High-frequency electron-spin-resonance measurements on Mn x Mg1-xO (x = 1.0×10-4) and DPPH at very low temperatures - Y Ishikawa; K Ohya; S Miura; Y Fujii; S Mitsudo; T Mizusaki; A Fukuda; A Matsubara; H Kikuchi; T Asano; H Yamamori; S Lee; et al. (United Kingdom, 2022)
We have developed a millimeter-wave electron-spin-resonance (ESR) system for very low temperatures (T < 1 K) that can be employed for nuclear-magnetic-resonance measurements by using dynamic nuclear polarization. The system uses a Fabry-Pérot resonator that works in the frequency range of 125 – 130 GHz and covers the temperature range of 0.09 – 6.5 K. We have performed ESR measurements in the frequency around 128 GHz by using Mn x Mg1-x O (x = 1.0 × 10-4) and free-radical samples of 1, 1-diphenyl-2-picrylhydrazyl (DPPH), because these samples have been proposed as field and sensitivity markers. Temperature dependence of the ESR signal intensity for Mn x Mg1-x O shows anomalies originating from magnetic order are found around 3.5 – 4 K. We estimate the sensitivity of the system for ESR detections to be 6 × 1013 spins/G at 5.8 K. Because DPPH shows no observable shift in the magnetic field, we propose it as a useful standard marker for ESR measurements at very low temperatures.
28th International Conference on Low Temperature Physics (LT28) 9–16 August 2017, Gothenburg, Sweden